The support of the european union to the alternative development programs in colombia: cooperation to combat against terrorism and illicit drugs trafficking (2009)
This article presents an empirical analysis of the European Union cooperation with Colombia in development programs for areas with illicit crops, so-called alternative development programs. The central idea is that this cooperation is part of the EU international policy against illicit drug trafficking. EU support for alternative development programs meant to counter the illegal export of cocaine to the European market. In Colombia, the dynamics of negotiation and implementation of this cooperation has helped to strengthen government programs of alternative development and policies against terrorism and production and export illicit narcotics.The article initially describes the transformation of the support of European cooperation to the peace policy towards the support of the “democratic security” policy. Then it highlights the complementarity between EU policies and the Colombian Government on alternative development and explains the meaning of the use of development aid policies in the “fight against drugs”. Conclusion argues the need to revise the multilateral agreement that guides the policies of development cooperation for areas with illicit crops: the United Nations Convention against Illicit Traffic in Narcotic Drugs and Psychotropic Substances, signed in 1988.